Post-infiltration to improve the density of binder jetting ceramic parts. Issue 15 (December 2022) - Chen, Qirong; Juste, Enrique; Lasgorceix, Marie; Lefebvre, Guillaume; Tenailleau, Christophe; Duployer, Benjamin; Grossin, David; Petit, Fabrice; Leriche, Anne
Abstract: Infiltration of printed bodies with a ceramic suspension is a relevant approach to enhance density and properties of the porous binder-jetted parts. In the present work, significant improvements of alumina parts processed through this combination printing-infiltration was reported. The density of non-infiltrated (but sintered) samples only reached 55.3 ± 1.1% of the theoretical density while it raised up to 87.9 ± 0.5% after infiltration of a pre-consolidated body followed by sintering. Influence of multi-infiltration operations, pre-consolidation temperature, solids loading of suspensions and duration of infiltration on the final part density were discussed. Infiltration mechanism and porosity distribution have been carefully investigated. It was demonstrated that the ceramic suspension infiltrated the pre-consolidated ceramic skeleton mostly under the effect of gravity which may result in density heterogeneities of the infiltrated parts. The reported processing route can be straightforwardly applied to other ceramic systems and is particularly inexpensive, and it is believed to have industrial relevance.